Towards a comparative and integrative framework for regulatory oversight of online advertising: Challenges, mitigation strategies, outcomes, and areas of intervention - Advait Deshpande; Lucie Lechardoy; Francisco Lupiá\~nez-Villanueva (International Telecommunications Society (ITS), 2022)
As the online advertising market has grown, issues such as high volume of ads, highly personalised and targeted ads, the role of algorithmic biases, lack of transparency of ad placement, and complex financial flows in the ad tech supply chain have received increased attention in academic and popular literature. Despite concerted efforts within the industry and legislative action at national and international levels, available measures to monitor and detect these challenges are often perceived to lag behind increasing layers of intermediation and ever-increasing footprint of the online platforms. The aim of this paper is to discuss how a comparative and integrative framework for regulatory oversight of online advertising could be assembled. For this purpose, the paper draws on a literature review of peer-reviewed articles and grey literature to identify the challenges in online advertising, known mitigation strategies, and possible outcomes of the strategies. As part of the initial specification of the framework developed, the paper covers broad categories of market players, type of challenges, mitigation strategies, and intended outcomes for regulatory oversight of online advertising. Additional areas for investigation and potential improvement of the draft framework are also identified. The ideas discussed in this paper are expected to be of interest to digital economy researchers, policy researchers and policy makers, various players in the online advertising supply chain, public and private sector stakeholders monitoring and investigating the online advertising ecosystem, and anyone interested in balancing the economic gains of online advertising against the challenges it poses to the platform end-users and the wider online platform economy.
Keywords: 330; Online advertising; Online platforms; Platform regulation; Technology policy